1999
DOI: 10.1016/s0886-3350(99)00203-5
|View full text |Cite
|
Sign up to set email alerts
|

Combined cataract surgery, intraocular lens implantation, and viscocanalostomy1

Abstract: Combined viscocanalostomy, cataract extraction, and IOL implantation was safe and efficacious in lowering IOP whether a shared scleral incision or a separate clear corneal incision was used for phacoemulsification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 19 publications
0
13
0
2
Order By: Relevance
“…28,30,[32][33][34]37,38 In the current study, the magnitude of the IOP reduction was among the lowest that has been reported after viscocanalostomy or phacoviscocanalostomy; studies report reductions ranging from 5.4 mm Hg to 30.5 mm Hg. 25,28,[30][31][32][33][34][35][36][37][38] Regarding the difference in surgical outcomes, race, observation periods, preoperative IOP levels, surgical success criteria, preoperative or postoperative medication use, and surgeon experience may have contributed to the wide variations in IOP reduction. Jongsareejit et al 6 report that only about 40% of Japanese patients with NTG successfully maintained an IOP level 20% lower than the preoperative IOP after trabeculectomy with MMC.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…28,30,[32][33][34]37,38 In the current study, the magnitude of the IOP reduction was among the lowest that has been reported after viscocanalostomy or phacoviscocanalostomy; studies report reductions ranging from 5.4 mm Hg to 30.5 mm Hg. 25,28,[30][31][32][33][34][35][36][37][38] Regarding the difference in surgical outcomes, race, observation periods, preoperative IOP levels, surgical success criteria, preoperative or postoperative medication use, and surgeon experience may have contributed to the wide variations in IOP reduction. Jongsareejit et al 6 report that only about 40% of Japanese patients with NTG successfully maintained an IOP level 20% lower than the preoperative IOP after trabeculectomy with MMC.…”
Section: Discussionmentioning
confidence: 76%
“…23,28 Viscocanalostomy, which relies on the free flow of aqueous through a ''window'' into a ''lake,'' effectively reduces IOP and is safe. 25,[28][29][30][31][32][33][34][35][36][37][38][39] Although studies have shown that viscocanalostomy reduces IOP in patients with high-tension POAG, 28,29,34,39 it is unclear whether it has a positive IOP-lowering effect in patients with NTG. Regarding combined surgery, it is also unclear whether patients are better served by combined viscocanalostomy and cataract surgery or whether cataract surgery only is sufficient to maintain quality of life.…”
mentioning
confidence: 99%
“…Isolated or combined with phacoemulsification, both procedures may offer good success rates, minimizing the risk for postoperative complications associated with trabeculectomy or phacotrabeculectomy. [3][4][5][6][7][8][9][10] Regarding the efficacy of these nonpenetrating filtration procedures, the results are controversial. 4,11 Recently, Shaarawy et al 12 found that variability in the results of deep sclerectomy was associated with differences in the mean IOP achieved on the first postoperative day.…”
mentioning
confidence: 99%
“…As opposed to phacotrabeculectomy, combined phaco-DS has better outcomes in terms of IOP control than DS alone [68]. Phacotrabeculectomy and phaco-DS showed no statistical difference in the IOP control although the phacotrabeculectomy groups tend to have lower IOP.…”
Section: Discussionmentioning
confidence: 78%